Gender issues in an individual’s relationship with authority: Qualitative analysis of subjective experience - Bieliauskienė, Ieva; Gudaitė, Gražina (Psichologija, 2016)
An experience of a relationship to authority, which we understand as a person or institution superior in its competence, knowledge, wisdom or power, can be considered a universal human experience. Different theoretical publications and our own research suggest that gender issues are significant in an individual’s relationship to authority figures: feminine and maternal authority seems to be denied in favour of male and paternal authority, also the ways of relating to authority typical of men and women, as our earlier research shows, may be rather different. In this study, we explore the subjective experience of their relationship to authority of both genders of 8 men and 8 women belonging to two age groups: 22–25 years old and 44–49 years old. These age groups were chosen because of the historical context in Lithuania: the representatives of the elder group were born and grew up under the authoritarian regime of the Soviet Union, and the younger group were born already after Lithuania restored its independence in 1990. Thematic analysis of the semi-structured interviews let us identify 5 main themes: Resistance against authority; Availability of authority; Denial of authority; Recognition of authority; Similarity with authority. Our female participants had a closer and more personalised relationship, especially with female authority figures, and men had a more distant and rational relationship to authority. The authority of at least one parent was usually denied, with father’s authority denied mostly because of his passivity and detachment from the family, while mothers were not considered authority because of their dominance, wish to control and high emotionality. All the elder participants had a strong need to resist authority rebelling against it, however, female participants also revealed situations of obeying their authority figures while men rejected the possibility to obey. The younger male participants’ relationship to authority was more similar to the one more typical of the female participants in its tendency to be close, personalised and based on identification. These results point to the need to continue exploring the relationship to authority of men and women of different generations in Lithuania, looking for the ways to encourage a more constructive and less defensive communication with figures of authority.